HUBUNGAN PENGETAHUAN DAN KEYAKINAN DENGAN EFIKASI DIRI PENYANDANG DIABETIC FOOT ULCER - Rias, Yohanes Andy (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: to reveal whether the self-management of individuals and families includes the process of self-management (knowledge and belief, the ability of self-regulation, and social facilities), the proximal (self-behavior) include a summary of the activity of self-care diabetes in participants Diabetic Food Ulcer effect on health locus of control (HLOC) with Diabetic Food Ulcer complication in Bantul, Yogyakarta. Methods: cross sectional approach conducted in Bantul, Yogyakarta. Population in this study was all Type 2 DM patients with Diabetic Food Ulcer totaling 49 people. Number of 30 samples by random sampling technique. Independent variables are knowledge and confidence so the dependent variable was analyzed using self-efficacy test rho spearmen statistic.Results: Statistical test results using spearmen rho with a significance value of p = 0.017 is smaller than the specified p <0.05 then the hypothesis is accepted. Conclusion: There is a relationship between knowledge and beliefs with self-efficacy. Necessary to study psychosocial factors in patients with Diabetic Food Ulcer associated with self-efficacy